2018
DOI: 10.1002/jmri.26274
|View full text |Cite
|
Sign up to set email alerts
|

Rapid compositional mapping of knee cartilage with compressed sensing MRI

Abstract: More than one decade after the introduction of compressed sensing (CS) in MRI, researchers are still working on ways to translate it into different research and clinical applications. The greatest advantage of CS in MRI is the reduced amount of k-space data needed to reconstruct images, which can be exploited to reduce scan time or to improve spatial resolution and volumetric coverage. Efficient data acquisition using CS is extremely important for compositional mapping of the musculoskeletal system in general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 111 publications
0
35
0
Order By: Relevance
“…Several studies have demonstrated that compressed sensing (CS)‐based methods can accelerate T 1 ρ mapping . CS is particularly suitable for T 1 ρ mapping because of the high image compressibility along the parametric direction.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that compressed sensing (CS)‐based methods can accelerate T 1 ρ mapping . CS is particularly suitable for T 1 ρ mapping because of the high image compressibility along the parametric direction.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike standard NUFFT‐based magnitude noise profiles which follow a well‐known Rayleigh distribution, the statistical characteristics of noise from iterative reconstruction are still not fully understood. The effects on statistical and spatial noise distribution may however bias the estimation of other parameters such as T2 …”
Section: Discussionmentioning
confidence: 99%
“… λ is the regularization parameter, and T is the sparsifying transform. Here the sparsifying transform used was spatial temporal finite differences (STFD) with the temporal order set to 1 and the spatial order set to 1 . The value of λ was determined by running a series of test values on a log scale for one dataset and using that value for subsequent reconstructions .…”
Section: Methodsmentioning
confidence: 99%
“…The value of λ was determined by running a series of test values on a log scale for one dataset and using that value for subsequent reconstructions . In this version of GRASP, fast iterative shrinkage thresholding algorithm with fast gradient projection (FISTA‐FGP) was used for minimization of the cost function …”
Section: Methodsmentioning
confidence: 99%